Pendampingan Pelayanan Kunjungan Neonatal Dengan Pendekatan Home Care Menggunakan Aplikasi Telemonitoring di Wilayah Kerja Puskesmas Mabelopura Kota Palu - Rizkiyati, Ita (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Neonatal visits are important for monitoring newborn health, yet limited access is often a constraint. This activity aims to accompany families in neonatal visiting services with a home care approach using a telemonitoring application in the working area of Mabelopura Health Centre, Palu City. Methods include socialization, application training, and family accompaniment. Results showed improved family understanding, app usage skills, as well as healthcare personnel’s ease in monitoring the baby’s condition remotely. This approach effectively supports neonatal services and can potentially be developed sustainably.